Topic modeling for frame analysis: A study of media debates on climate change in India and USA. (April 2022) - Ylä-Anttila, Tuukka; Eranti, Veikko; Kukkonen, Anna
We argue that 'topics' of topic models can be used as a useful proxy for frames if (1) frames are operationalized as connections between concepts; (2) theme-specific data are used; and (3) topics are validated in terms of frame analysis. Demonstrating this, we analyse 12 climate change frames used by NGOs, governments and experts in Indian and US media, gathered by topic modeling. We contribute methodologically to topic modeling in the social sciences and frame analysis of public debates, and empirically to research on climate change media debates.